Persistent Oxidative Stress and Inflammasome Activation in CD14highCD16− Monocytes From COVID-19 Patients - Lage, Silvia Lucena; Amaral, Eduardo Pinheiro; Hilligan, Kerry L.; Laidlaw, Elizabeth; Rupert, Adam; Namasivayan, Sivaranjani; Rocco, Joseph; Galindo, Frances; Kellogg, Anela; Kumar, Princy; Poon, Rita; Wortmann, Glenn W.; et al. (Frontiers in Immunology, 2022)
The poor outcome of the coronavirus disease-2019 (COVID-19), caused by SARS-CoV-2, is associated with systemic hyperinflammatory response and immunopathology. Although inflammasome and oxidative stress have independently been implicated in COVID-19, it is poorly understood whether these two pathways cooperatively contribute to disease severity. Herein, we found an enrichment of CD14highCD16- monocytes displaying inflammasome activation evidenced by caspase-1/ASC-speck formation in severe COVID-19 patients when compared to mild ones and healthy controls, respectively. Those cells also showed aberrant levels of mitochondrial superoxide and lipid peroxidation, both hallmarks of the oxidative stress response, which strongly correlated with caspase-1 activity. In addition, we found that NLRP3 inflammasome-derived IL-1 secretion by SARS-CoV-2-exposed monocytes in vitro was partially dependent on lipid peroxidation. Importantly, altered inflammasome and stress responses persisted after short-term patient recovery. Collectively, our findings suggest oxidative stress/NLRP3 signaling pathway as a potential target for host-directed therapy to mitigate early COVID-19 hyperinflammation as well as its long-term outcomes.